Economic conditions in Egypt in the fourth century AH Through the book “Al-Diyarat” by Shabishti (d. 388 AH / 998 AD) - Muhaisen, Maryam Haider Mohi; Al-Suwaidi, Hazem Wattan Hindi (Al-Adab Journal, 2021)
The study of social history is one of the important historical topics for providing us with information and pictures on the nature of social life that people lived in the Arab Islamic State, and sheds light on the most important social aspects of Islamic societies, which have not been used in the past enough efforts to reveal it and make it visible. The Fatimid state witnessed a boom in the economic life in Egypt. This is evident in the manifestations of the extravagance and luxury experienced by the state, especially after the arrival of the Fatimid Caliph al-Mu'izz Dinullah (341-365 AH / 952-975 AD) Fatimid to Egypt. This is because of the money and gems that Al-Mu'izz's religion campaigned with him when he came to Egypt.